Revitalisasi Keharmonisan Dunia (Menilik Relevansi Antara Moral, Agama, dan Bencana) - Enriko Tedja Sukmana (UIN Sunan Kalijaga Yogyakarta, 2013)
The existence of the world is getting older impact to the vulnerability of natural structure that ultimately ended the catastrophic events known. But, consciously or not, natural disasters are not always started from the already fragile condition of the world, but it was related to human intervention in the process. Morality is the basic for the creation of a harmony, not only between man and man but a man by nature, started to abandoned and forgotten, made worse by the existence of religion is often only seen as mere appendages identity. Impact, the stability of the world that has been designed in such a way by God became unstable and fragile, that lead to the occurrence of damage and natural disasters. In order to repair and restore the world's harmony, people are required to understand the values of morality and the nature of religion, because it should be the value of morality and religion become the main reference in behaving.